Analysis of Early MP-ASI Giving and Relationship with Incidence of Diarrhea in Babies 0-6 Months in the District Medan Tuntungan - Barirah; Ira Maulani Lubis (Cattleya Darmaya Fortuna, 2025)
Complementary foods for breast milk are foods that are given to babies who are 6 months old or older because breast milk does not meet the nutritional needs of babies. Mother's knowledge of MP-ASI is very important so that mothers can give MP ASI to the baby appropriately. Mother's lack of knowledge about the importance of MP-ASI is influenced by the promotion of dietary supplements and formula milk products. Early MP-ASI with the incidence of diarrhea in 0-6 month infants affects the mother's access to the time media that influences decision-making, where the higher the mother's education, the greater the opportunity to provide MP-ASI. The study aims to analyze the early MP-ASI feeding with the incidence of diarrhea in infants 0-6 months with feeding to infants. The type of research is analytical correlative with the design of a cross sectional study. The research was carried out in Medan Tuntungan District, starting from September-December 2025. The population and sample in the study of all mothers who had babies in Medan Tuntungan District amounted to 54 people. Sampling is a total sampling technique. The study used the chi-square test with a total of 54 research samples. Respondents were given a questionnaire to find out the early MP-ASI with the incidence of diarrhea in babies 0-6 months of administration. The results of the data obtained were tested using chi-square test statistics with α=0.05. The results showed that there was a significant relationship between early MP-breastfeeding and the incidence of diarrhea in infants 0-6 months, with a probability value (p = 0.000). The results showed that there was a significant significant relationship between early MP-breastfeeding and the incidence of diarrhea in infants 0-6 months, with a probability value (p = 0.000). The research team's suggestion is that it is necessary to carry out a health education program for mothers who have babies aged 0-6 months, coaching and empowerment to mothers in Medan Tuntungan District about the benefits and effects of not giving MP-ASI to babies 0-6 months with the incidence of diarrhea, in order to increase maternal knowledge, change maternal behavior about the importance of giving MP-ASI to babies 0-6 months with the incidence of diarrhea